Stereolithographic 3D printing (SLA 3DP) of pharmaceutical tablets: 3DP tablets (Transactions on Additive Manufacturing Meets Medicine, 2019)
We evaluated the applicability of SLA 3DP in making pharmaceutical tablets. Adding alizarin dye in the printing polymers improved print resolution through minimizing light scattering. 3DP tablets were evaluated for weight deviation, uniformity in drug content and dissolution profiles. 3DP tablets were determined to be uniform in weight and drug content based on European Pharmacopoeia criteria. Tablets with different sizes and shapes were printed with consistency. A lower PEGDA to PEG ratio, addition of xylitol as disintegrant and change in tablet design to improve the surface area-to-volume ratio, were explored to improve rate of drug release from 3DP tablets.